Diamond grinding wheel and preparation method and application thereof

By using specific auxiliary adhesives in diamond grinding wheels, the bonding force between diamond abrasives and metal powder is improved, the problem of abrasive peeling is solved, and the high-quality thinning effect of silicon carbide wafers is achieved.

CN119681802APending Publication Date: 2025-03-25JIANGSU CHAOXINXING SEMICON CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411913162.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing metal bonding agent diamond grinding wheels have problems of abrasive peeling during use, resulting in a decrease in the grinding quality and efficiency of silicon carbide wafers.

Method used

By introducing specific auxiliary adhesives, such as long-chain silane coupling agents, polyethylene glycol fatty acid esters and polyethylene glycol, the binding force between diamond abrasives and metal powder is improved, the interface tension is reduced, the bonding effect is enhanced, and the abrasives are prevented from falling off.

Benefits of technology

The efficient combination of diamond and metal bonding agent is achieved, and the wear ratio is avoided to remove abrasives, which improves the high-quality thinning effect of silicon carbide wafers. The surface TTV value is less than 4μm, the roughness Ra is 14-25nm, and the wear ratio is ≤1:3.0.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206234940000021
    Figure BDA0005206234940000021
  • Figure BDA0005206234940000071
    Figure BDA0005206234940000071
  • Figure BDA0005206234940000171
    Figure BDA0005206234940000171
Patent Text Reader

Abstract

The invention relates to a diamond grinding wheel and a preparation method and application thereof, in particular to the technical field of precision machining.The diamond grinding wheel is composed of, by mass, 25%-50% of diamond grinding materials, 45%-70% of metal binding agents and 4%-8% of auxiliary binding agents; wherein the auxiliary adhesive comprises a long-chain silane coupling agent, polyethylene glycol fatty acid ester and polyethylene glycol. According to the diamond grinding wheel provided by the invention, by introducing the specific auxiliary adhesive, the binding force of the diamond abrasive and the metal powder is improved, meanwhile, the interfacial tension between the metal powder and the diamond abrasive is reduced, and the wettability is improved, so that the surface of the diamond abrasive can be better coated with the metal powder; and therefore, efficient bonding of the diamond and the metal bonding agent is achieved, and falling of the abrasive in the using process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of precision machining, and in particular to a diamond grinding wheel and a preparation method and application thereof. Background Art

[0002] At present, silicon carbide wafers are an important representative of the third generation of high-performance semiconductor wafers. The processing quality and precision of SiC wafers directly affect the performance of semiconductor devices. Ultra-precision grinding of silicon carbide is to further process the wafer surface on the basis of rough grinding and thinning to achieve a lower surface roughness to meet the use requirements of various high-precision components. The processed SiC wafers are required to have a damage-free, defect-free, and low-roughness surface to meet the use requirements of ultra-precision components.

[0003] The binder used to consolidate abrasive grains in superhard abrasive tools is a key factor affecting the performance of superhard abrasive tools. Common binders include resin binder, ceramic binder, rubber binder and metal binder.

[0004] For example, CN106985085A discloses a metal bond diamond grinding wheel, which is composed of metal powder, copper-cerium alloy, pore-forming agent, TS-1 titanium silicon molecular sieve, and diamond composite abrasive; the metal powder is iron powder, copper powder, nickel powder, and tin powder; the pore-forming agent is a PE / CeO2 / Cu composite; and the diamond composite abrasive is a diamond / cerium oxide core-shell composite abrasive.

[0005] Although metal binders have good strength, toughness and heat resistance, there is usually a problem that the binder and the abrasive cannot form a chemical metallurgical bond. Therefore, the abrasive is only mechanically embedded in the binder and has limited holding force. The abrasive particles may fall off easily, causing the grinding wheel to fail, thereby reducing the grinding quality and efficiency of the silicon carbide wafer. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a diamond grinding wheel and a preparation method and use thereof, so as to solve the defect that the abrasive grains fall off due to the poor bonding ability of the metal binder.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 25-50% diamond abrasive, 45-70% metal binder and 4-8% auxiliary binder;

[0009] Wherein, the auxiliary adhesive comprises: a long-chain silane coupling agent, polyethylene glycol fatty acid ester and polyethylene glycol; the structural formula of the long-chain silane coupling agent is as follows:

[0010]

[0011] In the formula, R 1 Selected from H or -CH3, R 2 One selected from -OCH3, -OCH2CH3 or -OCH2CH2OCH3, R 3 is selected from H or -CH3, p is an integer of 1-20, q is an integer of 1-20, and x is an integer of 4-20.

[0012] The diamond grinding wheel provided by the present invention improves the bonding force between the diamond abrasive and the metal powder by introducing a specific auxiliary adhesive, and at the same time reduces the interfacial tension between the metal powder and the diamond abrasive, thereby improving the wettability, so that the metal powder can be better coated on the surface of the diamond abrasive, thereby achieving efficient bonding between the diamond and the metal binder, and avoiding the shedding of the abrasive during use.

[0013] As a preferred technical solution of the present invention, the particle size D50 of the diamond abrasive is 1-10 μm.

[0014] As a preferred technical solution of the present invention, the metal binder includes: aluminum powder, copper powder and titanium powder.

[0015] As a preferred technical solution of the present invention, the metal binder is composed of the following materials in terms of mass percentage: 60-80% aluminum powder, 10-30% copper powder and 5-15% titanium powder.

[0016] As a preferred technical solution of the present invention, the particle size D50 of the aluminum powder is 10-100 μm.

[0017] Preferably, the particle size D50 of the copper powder is 10-100 μm.

[0018] Preferably, the particle size D50 of the titanium powder is 10-100 μm.

[0019] As a preferred technical solution of the present invention, the auxiliary adhesive is composed of the following materials in terms of mass percentage: 20-40% long-chain silane coupling agent, 20-40% polyethylene glycol fatty acid ester and 30-50% polyethylene glycol.

[0020] As a preferred technical solution of the present invention, the polyethylene glycol fatty acid ester includes: one or a combination of at least two of polyethylene glycol monooleate, polyethylene glycol monostearate or polyethylene glycol monolaurate.

[0021] Preferably, the molecular weight of the polyethylene glycol fatty acid ester is 2000-6000.

[0022] Preferably, the molecular weight of the polyethylene glycol is 400-1000.

[0023] In a second aspect, the present invention provides a method for preparing the diamond grinding wheel as described in the first aspect, the preparation method comprising:

[0024] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel.

[0025] As a preferred technical solution of the present invention, the sintering is carried out under a protective atmosphere.

[0026] Preferably, the sintering temperature is 800-1000°C.

[0027] Preferably, the sintering holding time is 0.5-2h.

[0028] In a third aspect, the present invention provides a use of the diamond grinding wheel as described in the first aspect, the use comprising: being applied to one or at least two sections in the process of preparing silicon carbide single crystals including rough grinding, fine grinding, fine grinding, polishing pre-treatment or wafer back grinding.

[0029] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0030] (1) In the diamond grinding wheel provided by the present invention, the metal binder serves as an adhesive for the diamond abrasive, and its main function is to firmly fix the diamond abrasive grains on the grinding wheel substrate by sintering to form a whole, thereby maintaining the integrity of the grinding wheel. Aluminum is the main component of the binder, and has a low melting point and good ductility. It can form alloys with other metals to improve the comprehensive performance of the material; copper powder can improve the hardness and wear resistance of the material and enhance the mechanical strength of the material; titanium powder can significantly improve the hardness and strength of the material and enhance the high temperature resistance of the material; the auxiliary adhesive can further improve the bonding force between the diamond abrasive and the metal binder, thereby improving the wear resistance of the grinding wheel.

[0031] (2) The auxiliary adhesive used in the diamond grinding wheel provided by the present invention improves the bonding effect of the metal binder and the diamond abrasive through the synergistic cooperation of the three. Among them, the long-chain silane coupling agent has a methacryloyl group and a siloxane group, which can form a chemical bond with the hydroxyl group on the metal surface and the carbon atom on the diamond surface, thereby improving the bonding force between the diamond abrasive and the metal powder, and at the same time can reduce the interfacial tension between the metal powder and the diamond abrasive, improve the wettability, and enable the metal powder to be better coated on the surface of the diamond abrasive; the good surface activity and film-forming property of the polyethylene glycol fatty acid ester bond the diamond abrasive and the metal powder together to prevent them from separating during the mixing process, thereby improving the uniform dispersion and bonding strength of the diamond abrasive and the metal powder during the preparation process; the polyethylene glycol can well and evenly disperse the long-chain silane coupling agent and the polyethylene glycol fatty acid ester, thereby ensuring the consistency and uniformity of the auxiliary adhesive.

[0032] (3) The diamond grinding wheel provided by the present invention can achieve high-quality thinning of silicon carbide wafers. The surface TTV value of the silicon carbide wafer obtained after thinning is less than 4μm, the roughness Ra is 14-25nm, and the wear ratio (μm / wafer) is ≤1:3.0; under the preferred embodiment, the surface TTV value of the silicon carbide wafer obtained is less than 2μm, the roughness Ra is 13-20nm, and the wear ratio (μm / wafer) is ≤1:2.5. DETAILED DESCRIPTION

[0033] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0034] This embodiment provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 25-50% diamond abrasive, 45-70% metal binder and 4-8% auxiliary adhesive.

[0035] The raw material diamond abrasive used in the diamond grinding wheel has a mass percentage of 25-50%, for example, 25%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, etc., but is not limited to the listed values, and other values ​​not listed within this range also meet the requirements.

[0036] Among them, the raw metal binder used in the diamond grinding wheel is 45-70%, 45%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66% or 68% by mass, but is not limited to the listed values. Other values ​​not listed within this range also meet the requirements.

[0037] Among them, the raw material auxiliary binder used in the diamond grinding wheel is 4-8% by mass percentage, for example, it can be 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%, 7.2%, 7.4%, 7.6%, 7.8% or 8%, etc., but is not limited to the listed values, and other values ​​not listed within this range also meet the requirements.

[0038] Wherein, the particle size D50 of the diamond abrasive is 1-10 μm.

[0039] In the present invention, the diamond abrasive grains used can be selected from natural diamond abrasive grains, single crystal artificial diamond abrasive grains or polycrystalline diamond abrasive grains, or a combination of at least two of them.

[0040] Exemplarily, the combinations of diamond abrasive grains used are as follows: a combination of natural diamond abrasive grains and single-crystal artificial diamond abrasive grains, a combination of single-crystal artificial diamond abrasive grains and polycrystalline diamond abrasive grains, a combination of natural diamond abrasive grains and polycrystalline diamond abrasive grains, and a combination of natural diamond abrasive grains, single-crystal artificial diamond abrasive grains, and polycrystalline diamond abrasive grains.

[0041] Wherein, the metal binder includes: aluminum powder, copper powder and titanium powder.

[0042] The metal binder is composed of the following materials in terms of mass percentage: 60-80% aluminum powder, 10-30% copper powder and 5-15% titanium powder.

[0043] Among them, the aluminum powder used in the metal binder is 60-80% by mass percentage, for example, it can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78% or 80%, etc., but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0044] The copper powder used in the metal binder has a mass percentage of 10-30%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0045] Among them, the titanium powder used in the metal binder is 5-15% by mass percentage, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., but is not limited to the listed values, and other values ​​not listed within this range also meet the requirements.

[0046] Wherein, the particle size D50 of the aluminum powder is 10-100 μm.

[0047] Wherein, the particle size D50 of the copper powder is 10-100 μm.

[0048] Wherein, the particle size D50 of the titanium powder is 10-100 μm.

[0049] Wherein, the auxiliary adhesive comprises: a long-chain silane coupling agent, polyethylene glycol fatty acid ester and polyethylene glycol.

[0050] The auxiliary adhesive is composed of the following materials in terms of mass percentage: 20-40% of long-chain silane coupling agent, 20-40% of polyethylene glycol fatty acid ester and 30-50% of polyethylene glycol.

[0051] In the present invention, the long-chain silane coupling agent used in the auxiliary adhesive is 20-40% by mass, for example, it can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%, etc., but is not limited to the listed values, and other values ​​not listed within this range also meet the requirements.

[0052] In the present invention, the polyethylene glycol fatty acid ester used in the auxiliary adhesive is 20-40% by mass, for example, it can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%, etc., but is not limited to the listed values, and other values ​​not listed within this range also meet the requirements.

[0053] In the present invention, the weight percentage of polyethylene glycol used in the auxiliary adhesive is 30-50%, for example, it can be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, etc., but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0054] Among them, the structural formula of the long-chain silane coupling agent used is as follows:

[0055]

[0056] In the formula, R 1 Selected from H or -CH3, R 2 One selected from -OCH3, -OCH2CH3 or -OCH2CH2OCH3, R 3 is selected from H or -CH3, p is an integer of 1-20, q is an integer of 1-20, and x is an integer of 4-20.

[0057] Wherein, the long-chain hydroxyl-terminated silane coupling agent is prepared by conventional techniques in the art or is a commercially available product.

[0058] Exemplarily, the preparation process of the long-chain terminal hydroxyl silane coupling agent is as follows: a long-chain terminal hydroxyl acrylate and a double bond-containing silane coupling agent in a mass ratio of (0.8-1.2):1 are subjected to free radical polymerization reaction, for example, it can be 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.02:1, 1.04:1, 1.06:1, 1.08:1, 1.1:1, 1.12:1, 1.14:1, 1.16:1, 1.18:1 or 1.2:1, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0059] Wherein, the long-chain hydroxyl-terminated acrylate is selected from polyethylene glycol acrylate and / or polyethylene glycol methacrylate.

[0060] In the present invention, the structural formula of the polyethylene glycol acrylate used is CH2=CH-COO-(CH2CH2O) n H, n is an integer of 4-20.

[0061] In the present invention, the structural formula of the polyethylene glycol methacrylate used is CH2=C(CH3)-COO-(CH2CH2O) m H, m are integers of 4-20.

[0062] Among them, the double bond-containing silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane with the structural formula CH2=C(CH3)COO-CH2CH2CH2-Si-(OCH3)3, vinyltri(β-methoxyethoxy)silane with the structural formula CH2=CH-Si-(OCH2CH2OCH3)3, vinyltrimethoxysilane with the structural formula CH2=CH-Si-(OCH3)3 or vinyltriethoxysilane with the structural formula CH2=CH-Si-(OCH2CH3)3, one or a combination of at least two thereof.

[0063] Illustratively, the combinations of double bond-containing silane coupling agents are as follows: a combination of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane, a combination of vinyltri(β-methoxyethoxy)silane and vinyltrimethoxysilane, a combination of vinyltrimethoxysilane and vinyltriethoxysilane, and the like.

[0064] The organic solvent used in the free radical polymerization reaction includes: one or a combination of at least two of toluene, xylene, n-butanol or n-butyl acetate.

[0065] Illustratively, the combination of organic solvents is as follows: a combination of toluene and xylene, a combination of xylene and n-butanol, a combination of n-butanol and n-butyl acetate, a combination of xylene and n-butyl acetate, and the like.

[0066] The initiator used in the free radical polymerization reaction includes: one or a combination of at least two of azobisisobutyronitrile, tert-butyl peroxy-2-ethylhexanoate or benzoyl peroxide.

[0067] Illustratively, the combination of initiators used includes a combination of azobisisobutyronitrile and tert-butyl peroxy-2-ethylhexanoate, a combination of tert-butyl peroxy-2-ethylhexanoate and benzoyl peroxide, and a combination of azobisisobutyronitrile, tert-butyl peroxy-2-ethylhexanoate and benzoyl peroxide.

[0068] The mass ratio of the initiator used in the free radical polymerization reaction to the total amount of monomers (including the sum of the mass of the long-chain hydroxyl-terminated acrylate and the double-bond silane coupling agent) is (0.01-0.04):1, for example, it can be 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1 or 0.04:1, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0069] Exemplarily, the detailed preparation process of the long-chain terminal hydroxyl silane coupling agent is as follows: in a closed reaction container, long-chain terminal hydroxyl acrylate, double bond silane coupling agent, and an organic solvent sufficient for the reaction are added in proportion, nitrogen is introduced into the reaction system, and after mixing evenly, the temperature is raised to 90-110° C., an initiator is added dropwise, and then the reaction is kept warm for 1-4 hours to obtain the long-chain terminal hydroxyl silane coupling agent.

[0070] Wherein, the polyethylene glycol fatty acid ester includes: one or a combination of at least two of polyethylene glycol monooleate, polyethylene glycol monostearate or polyethylene glycol monolaurate.

[0071] In the present invention, the molecular weight of the polyethylene glycol fatty acid ester used is 2000-6000.

[0072] Illustratively, the combinations of polyethylene glycol fatty acid esters are as follows: a combination of polyethylene glycol monooleate and polyethylene glycol monostearate, a combination of polyethylene glycol monostearate and polyethylene glycol monolaurate, a combination of polyethylene glycol monooleate and polyethylene glycol monolaurate, a combination of polyethylene glycol monooleate, polyethylene glycol monostearate and polyethylene glycol monolaurate, and the like.

[0073] The molecular weight of the polyethylene glycol is 400-1000, for example, 400, 450, 500, 550, 600, 650, 700, 750 or 800, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0074] Furthermore, this embodiment provides a method for preparing the aforementioned diamond grinding wheel, the preparation method comprising:

[0075] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel.

[0076] Among them, the material can be optionally dried before cold pressing, the powder can be optionally dried separately, or the material obtained after mixing can be dried. Exemplarily, the drying temperature is 100-150°C and the insulation time is 3-4h.

[0077] The drying temperature is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0078] The heat preservation time during drying is 3-4h, for example, it can be 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values. Other values ​​not listed in this range also meet the requirements.

[0079] The cold pressing process can be carried out according to the conventional forming process in the art, such as placing the mixed material in a mold for cold pressing with or without drying.

[0080] Wherein, the sintering is carried out under a protective atmosphere.

[0081] The protective atmosphere includes nitrogen, helium, neon or argon, etc., which are protective atmospheres that do not react with the cold-pressed blank.

[0082] Exemplarily, the combination of protective atmospheres may be selected as: a combination of nitrogen and helium, a combination of helium and neon, a combination of neon and argon, and the like.

[0083] Wherein, the sintering temperature is 800-1000°C, for example, it can be 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0084] The sintering holding time is 0.5-2h, for example, it can be 0.5h, 0.6h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, but is not limited to the listed values. Other values ​​not listed within the range also meet the requirements.

[0085] Furthermore, this embodiment provides uses of the aforementioned diamond grinding wheel, which includes: being applied to one or at least two stages of the silicon carbide single crystal preparation process including rough grinding, fine grinding, fine grinding, polishing pretreatment or wafer back grinding.

[0086] Exemplarily, the combination of uses of the diamond grinding wheel can be selected as: using the diamond grinding wheel in coarse grinding and fine grinding, using the diamond grinding wheel in fine grinding and fine grinding, using the diamond grinding wheel in rough grinding and pre-polishing, using the diamond grinding wheel in wafer back grinding and pre-polishing, using the diamond grinding wheel in coarse grinding, fine grinding, fine grinding, pre-polishing and wafer back grinding, etc.

[0087] Further, in order to illustrate the good use effect that can be achieved by the diamond grinding wheel provided by the present invention, the following practical examples are used for illustration, as follows:

[0088] Example 1

[0089] This embodiment provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 40% diamond abrasive, 54% metal binder and 6% auxiliary binder;

[0090] The particle size D50 of the diamond abrasive is 4 μm;

[0091] The metal binder is composed of the following materials by mass percentage: 70% aluminum powder, 20% copper powder and 10% titanium powder; the particle size D50 of the aluminum powder is 30 μm; the particle size D50 of the copper powder is 30 μm; the particle size D50 of the titanium powder is 90 μm;

[0092] The auxiliary adhesive is composed of the following materials by mass percentage: 30% of long-chain silane coupling agent (long-chain terminal hydroxyl silane coupling agent), 30% of polyethylene glycol fatty acid ester (polyethylene glycol monolaurate, molecular weight of 3000) and 40% of polyethylene glycol (molecular weight of 800).

[0093] The preparation process is as follows:

[0094] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel;

[0095] The sintering is carried out under a protective atmosphere (nitrogen), the sintering temperature is 900° C., and the holding time is 1.5 h.

[0096] The preparation process of the long-chain hydroxyl-terminated silane coupling agent used in this embodiment is as follows:

[0097] In a closed reaction container, long-chain hydroxy-terminated acrylate (polyethylene glycol methacrylate) and double-bond silane coupling agent (vinyl tri(β-methoxyethoxy) silane) in a mass ratio of 1:1 and an organic solvent (toluene, 1000 mL) were added in a proportion, nitrogen was introduced into the reaction system, and after mixing evenly, the temperature was raised to 100°C, and an initiator was added dropwise (the initiator was azobisisobutyronitrile, and the mass ratio of the initiator to the total amount of monomer (the total mass of the long-chain hydroxy-terminated acrylate and the double-bond silane coupling agent) was 0.02:1), and then the reaction was kept warm for 2 hours to obtain a long-chain hydroxy-terminated silane coupling agent.

[0098] Example 2

[0099] This embodiment provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 45% diamond abrasive, 48% metal binder and 7% auxiliary binder;

[0100] The particle size D50 of the diamond abrasive is 6 μm;

[0101] The metal binder is composed of the following materials by mass percentage: 63% aluminum powder, 25% copper powder and 12% titanium powder; the particle size D50 of the aluminum powder is 30 μm; the particle size D50 of the copper powder is 30 μm; the particle size D50 of the titanium powder is 80 μm;

[0102] The auxiliary adhesive is composed of the following materials by mass percentage: 35% of long-chain silane coupling agent (long-chain terminal hydroxyl silane coupling agent), 33% of polyethylene glycol fatty acid ester (polyethylene glycol monooleate, molecular weight 4000) and 32% of polyethylene glycol (molecular weight 600).

[0103] The preparation process is as follows:

[0104] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel;

[0105] The sintering is carried out under a protective atmosphere (helium), the sintering temperature is 950° C., and the holding time is 1 hour.

[0106] The preparation process of the long-chain hydroxyl-terminated silane coupling agent used in this embodiment is as follows:

[0107] In a closed reaction container, long-chain terminal hydroxyl acrylate (polyethylene glycol acrylate) and double-bond silane coupling agent (γ-(methacryloyloxy)propyltrimethoxysilane) and organic solvent (xylene, 1000 mL) were added in a proportion of 1.1:1, nitrogen was introduced into the reaction system, and after mixing evenly, the temperature was raised to 100°C, and the initiator (the initiator was tert-butyl peroxy-2-ethylhexanoate, and the mass ratio of the initiator to the total amount of monomer (the total mass of the long-chain terminal hydroxyl acrylate and the double-bond silane coupling agent) was 0.03:1) was added dropwise, and then the reaction was kept warm for 3 hours to obtain the long-chain terminal hydroxyl silane coupling agent.

[0108] Example 3

[0109] This embodiment provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 47% diamond abrasive, 45% metal binder and 8% auxiliary binder;

[0110] The particle size D50 of the diamond abrasive is 1 μm;

[0111] The metal binder is composed of the following materials by mass percentage: 80% aluminum powder, 15% copper powder and 5% titanium powder; the particle size D50 of the aluminum powder is 10 μm; the particle size D50 of the copper powder is 100 μm; the particle size D50 of the titanium powder is 10 μm;

[0112] The auxiliary adhesive is composed of the following materials in terms of mass percentage: 30% of a long-chain silane coupling agent (a long-chain hydroxyl-terminated silane coupling agent), 20% of polyethylene glycol fatty acid ester (polyethylene glycol monooleate and polyethylene glycol monolaurate in a mass ratio of 1:1, the molecular weight of polyethylene glycol monooleate is 2000, and the molecular weight of polyethylene glycol monolaurate is 3000), and 50% of polyethylene glycol (molecular weight is 400).

[0113] The preparation process is as follows:

[0114] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel;

[0115] The sintering is carried out under a protective atmosphere (argon), the sintering temperature is 800° C., and the holding time is 2 hours.

[0116] The preparation process of the long-chain hydroxyl-terminated silane coupling agent used in this embodiment is as follows:

[0117] In a closed reaction container, long-chain hydroxyl-terminated acrylate (polyethylene glycol acrylate), double-bond silane coupling agent (vinyl trimethoxysilane) and organic solvent (n-butanol, 1000 mL) were added in a proportion of 0.8:1 by mass, nitrogen was introduced into the reaction system, and after mixing evenly, the temperature was raised to 110°C, and the initiator (the initiator was benzoyl peroxide, and the mass ratio of the initiator to the total amount of monomer (the total mass of the long-chain hydroxyl-terminated acrylate and the double-bond silane coupling agent) was 0.01:1) was added dropwise, and then the reaction was kept warm for 1 hour to obtain the long-chain hydroxyl-terminated silane coupling agent.

[0118] Example 4

[0119] This embodiment provides a diamond grinding wheel, which is composed of the following raw materials in percentage by mass: 26% diamond abrasive, 70% metal binder and 4% auxiliary binder;

[0120] The particle size D50 of the diamond abrasive is 10 μm;

[0121] The metal binder is composed of the following materials by mass percentage: 60% aluminum powder, 25% copper powder and 15% titanium powder; the particle size D50 of the aluminum powder is 100 μm; the particle size D50 of the copper powder is 10 μm; the particle size D50 of the titanium powder is 100 μm;

[0122] The auxiliary adhesive is composed of the following materials by mass percentage: 20% long-chain silane coupling agent (long-chain terminal hydroxyl silane coupling agent), 40% polyethylene glycol fatty acid ester (polyethylene glycol monostearate, molecular weight of 2000) and 40% polyethylene glycol (molecular weight of 1000).

[0123] The preparation process is as follows:

[0124] The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel;

[0125] The sintering is carried out under a protective atmosphere (neon gas), the sintering temperature is 1000° C., and the holding time is 0.5 h.

[0126] The preparation process of the long-chain hydroxyl-terminated silane coupling agent used in this embodiment is as follows:

[0127] In a closed reaction container, long-chain terminal hydroxyl acrylate (polyethylene glycol methacrylate) and double-bond silane coupling agent (vinyl triethoxysilane) and organic solvent (n-butanol, 1000 mL) were added in a proportion of 1.2:1, nitrogen was introduced into the reaction system, and after mixing evenly, the temperature was raised to 90°C, and the initiator (the initiator was azobisisobutyronitrile, and the mass ratio of the initiator to the total amount of monomer (the total mass of the long-chain terminal hydroxyl acrylate and the double-bond silane coupling agent) was 0.04:1) was added dropwise, and then the reaction was kept warm for 4 hours to obtain the long-chain terminal hydroxyl silane coupling agent.

[0128] Comparative Example 1

[0129] The only difference from Example 1 is that the polyethylene glycol in the auxiliary binder is replaced by an equal amount of a long-chain silane coupling agent.

[0130] Comparative Example 2

[0131] The only difference from Example 1 is that the long-chain silane coupling agent in the auxiliary binder is replaced by an equal amount of polyethylene glycol fatty acid ester.

[0132] Comparative Example 3

[0133] The only difference from Example 1 is that the long-chain silane coupling agent in the auxiliary adhesive is replaced by an equal amount of acrylic emulsion.

[0134] Comparative Example 4

[0135] The only difference from Example 1 is that the polyethylene glycol fatty acid ester and polyethylene glycol in the auxiliary binder are replaced by an equal amount of a long-chain silane coupling agent.

[0136] Comparative Example 5

[0137] The only difference from Example 1 is that the polyethylene glycol fatty acid ester is replaced by an equal amount of pentaerythritol monooleate.

[0138] Comparative Example 6

[0139] The only difference from Example 1 is that the polyethylene glycol fatty acid ester, namely polyethylene glycol monolaurate, is replaced by an equal amount of lauroyl diethanolamide.

[0140] Comparative Example 7

[0141] The only difference from Example 1 is that the auxiliary binder is replaced by an equal amount of metal binder.

[0142] Comparative Example 8

[0143] The only difference from Example 1 is that the diamond grinding wheel is composed of the following raw materials in percentage by mass: 40% diamond abrasive, 50% metal binder and 10% auxiliary binder.

[0144] Comparative Example 9

[0145] The only difference from Example 1 is that the diamond grinding wheel is composed of the following raw materials in percentage by mass: 40% diamond abrasive, 58% metal binder and 2% auxiliary binder.

[0146] Example 5

[0147] The only difference from Example 1 is that the long-chain silane coupling agent, namely the long-chain hydroxyl-terminated silane coupling agent, is replaced by an equal amount of dodecyltrimethoxysilane.

[0148] Example 6

[0149] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 10% long-chain silane coupling agent, 40% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 50% polyethylene glycol.

[0150] Example 7

[0151] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 50% long-chain silane coupling agent, 20% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 30% polyethylene glycol.

[0152] Example 8

[0153] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 40% long-chain silane coupling agent, 10% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 50% polyethylene glycol.

[0154] Example 9

[0155] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 20% long-chain silane coupling agent, 50% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 30% polyethylene glycol.

[0156] Example 10

[0157] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 40% long-chain silane coupling agent, 40% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 20% polyethylene glycol.

[0158] Embodiment 11

[0159] The only difference from Example 1 is that the auxiliary adhesive is composed of the following materials by mass percentage: 20% long-chain silane coupling agent, 20% polyethylene glycol fatty acid ester (polyethylene glycol monolaurate) and 60% polyethylene glycol.

[0160] The diamond grinding wheel obtained in the above example was used to thin the silicon carbide wafer, and then the performance of the diamond grinding wheel was characterized. The results are shown in Table 1 below. The specific characterization process is as follows:

[0161] Flatness test: Use high-precision optical or mechanical measuring instruments to test the flatness of polished silicon carbide wafers and record the thickness values ​​at each point on the wafer surface. Data analysis: Input the measured data into a computer, perform data analysis using dedicated software, and calculate the TTV value of the wafer. The smaller the TTV value, the smaller the thickness change on the wafer surface and the higher the flatness.

[0162] Roughness test: Use atomic force microscopy to test the surface roughness of the chip. The smaller the roughness, the better the flatness.

[0163] Wear ratio test: Wear test is carried out using a wear tester. The smaller the wear ratio, the better the quality of the diamond grinding wheel.

[0164] Table 1

[0165]

[0166]

[0167] As can be seen from Table 1, the solution provided by the present invention uses a metal binder as an adhesive for diamond abrasives, and at the same time uses a specific auxiliary adhesive to enhance the bonding effect of the metal binder and the diamond abrasive grains through the synergistic cooperation of the components in the auxiliary adhesive, thereby achieving high-quality thinning of silicon carbide wafers.

[0168] It can be seen from Example 1 and Comparative Example 1 that without adding polyethylene glycol, the dispersion performance of the long-chain silane coupling agent and the polyethylene glycol fatty acid ester decreases, which ultimately affects the dispersion uniformity of the abrasive particles in the diamond grinding wheel, resulting in a decrease in the thinning quality of the silicon carbide wafer.

[0169] It can be seen from Example 1 and Comparative Example 2 that without adding a long-chain silane coupling agent, the bonding force between the diamond abrasive and the metal powder decreases, resulting in a decrease in the thinning quality of the silicon carbide wafer.

[0170] It can be seen from Example 1 and Comparative Example 3 that when the coupling agent does not use a long-chain silane coupling agent but uses an ordinary acrylic emulsion, the bonding force between the diamond abrasive and the metal powder decreases, resulting in a decrease in the thinning quality of the silicon carbide wafer.

[0171] It can be seen from Example 1 and Comparative Example 4 that the three auxiliary adhesives only retain the long-chain silane coupling agent. Although the bonding force between the diamond abrasive and the metal powder can be improved, the dispersion and uniformity of the diamond abrasive and the metal powder are reduced, resulting in uneven bonding strength of the diamond grinding wheel and reduced thinning quality.

[0172] It can be seen from Example 1 and Comparative Examples 5 and 6 that when the polyethylene glycol fatty acid ester is replaced with pentaerythritol monooleate or lauroyl diethanolamine, the film-forming properties of pentaerythritol monooleate and lauroyl diethanolamine are worse than those of the polyethylene glycol fatty acid ester, and the bonding strength of the diamond grinding wheel is weakened, which is not conducive to achieving high-quality thinning of silicon carbide wafers.

[0173] It can be seen from Example 1 and Comparative Example 7 that by removing the auxiliary binder and using an equal amount of metal complexing agent, the binding force between the diamond abrasive and the metal powder is significantly reduced without the auxiliary binder. At the same time, the uniform dispersion of the diamond abrasive and the metal powder is also reduced, the strength of the diamond grinding wheel is reduced, and the thinning quality is reduced.

[0174] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0175] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0176] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A diamond grinding wheel, characterized in that: The diamond grinding wheel is composed of the following raw materials in percentage by mass: 25-50% diamond abrasive, 45-70% metal binder and 4-8% auxiliary adhesive; Wherein, the auxiliary adhesive comprises: a long-chain silane coupling agent, polyethylene glycol fatty acid ester and polyethylene glycol; the structural formula of the long-chain silane coupling agent is as follows: In the formula, R 1 Selected from H or -CH3, R 2 One selected from -OCH3, -OCH2CH3 or -OCH2CH2OCH3, R 3 is selected from H or -CH3, p is an integer of 1-20, q is an integer of 1-20, and x is an integer of 4-20.

2. The diamond grinding wheel according to claim 1, characterized in that The particle size D50 of the diamond abrasive is 1-10 μm.

3. The diamond grinding wheel according to claim 1, characterized in that The metal binder comprises aluminum powder, copper powder and titanium powder.

4. The diamond grinding wheel according to claim 3, characterized in that: The metal binder is composed of the following materials in terms of mass percentage: 60-80% aluminum powder, 10-30% copper powder and 5-15% titanium powder.

5. The diamond grinding wheel according to claim 3 or 4, characterized in that: The particle size D50 of the aluminum powder is 10-100 μm; The particle size D50 of the copper powder is 10-100 μm; The particle size D50 of the titanium powder is 10-100 μm.

6. The diamond grinding wheel according to claim 1, characterized in that: The auxiliary adhesive is composed of the following materials in terms of mass percentage: 20-40% of a long-chain silane coupling agent, 20-40% of polyethylene glycol fatty acid ester and 30-50% of polyethylene glycol.

7. The diamond grinding wheel according to claim 1 or 6, characterized in that: The polyethylene glycol fatty acid ester includes: one or a combination of at least two of polyethylene glycol monooleate, polyethylene glycol monostearate or polyethylene glycol monolaurate; The molecular weight of the polyethylene glycol fatty acid ester is 2000-6000; The molecular weight of the polyethylene glycol is 400-1000.

8. A method for preparing a diamond grinding wheel as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises: The materials are mixed according to the formula of mass percentage, and then cold pressed and sintered in sequence to obtain a diamond grinding wheel.

9. The preparation method according to claim 8, characterized in that: The sintering is carried out under a protective atmosphere; The sintering temperature is 800-1000°C; The sintering holding time is 0.5-2h.

10. Use of the diamond grinding wheel according to any one of claims 1 to 7, characterized in that: The use includes: being applied to one or at least two sections of the process of preparing silicon carbide single crystals, including rough grinding, fine grinding, precision grinding, polishing pre-treatment or wafer back grinding.

Citation Information

Patent Citations

  • Diamond grinding wheel

    CN106625296A

  • Diamond grinding wheel for metal binding agent

    CN106985085A

  • Diamond grinding wheel and preparation method thereof

    CN108818329A

  • Improvements in and relating to the production of tools comprising diamond

    GB485565A

  • Super abrasive grain metal bond grinding wheel for precise cutting and its manufacture

    JP1999028669A